Double‐layered dual‐tuned RF coil using frequency‐selectable PIN‐diode control at 7‐T MRI. Issue 4 (21st May 2018) - Han, Sang‐Doc; Heo, Phil; Kim, Han‐Joong; Song, Hyunwoo; Kim, Donghyuk; Seo, Jeung‐Hoon; Ryu, Yeunchul; Noh, Young; Kim, Kyoung‐Nam
Abstract: This article presents a dual‐tuned (DT) radiofrequency (RF) coil for signal acquisition of 2 nuclei, namely, hydrogen ( 1 H) and sodium ( 23 Na), in the ultra‐high magnetic field of a 7‐T magnetic resonance imaging (MRI) system. The double‐layered dual‐tuned (DLDT) coil comprises a 2‐loop coil configuration per single‐pair geometry, with the 1 H and 23 Na coils being located on the outside and inside, respectively. The 1 H and 23 Na single‐pair elements are tuned to resonance frequencies of 297.20 and 78.61 MHz, respectively. The single‐pair geometry of the DLDT coil is extended to an 8‐pair configuration to cover the human head, and the operation mode is transmission/reception (Tx/Rx). The 8‐pair DLDT Tx/Rx coil array is designed with a non‐overlapped single pair between the 1 H coil elements for geometric decoupling, and capacitive decoupling is implemented to minimize the mutual inductance coupling. The 2 resonance frequencies are fed through a single RF port to a common matching board, and each frequency is selected using the voltages at both ends of a PIN diode. Through use of the PIN diode in the DLDT coil configuration, with a voltage drop at both ends, different resonance frequencies can be selected for each coil element in accordance with the diode ON/OFF state. The experiments conducted showed that the proposed DLDT coil is effective in acquiring signals of 1 H and 23 Na in the MRI system.